2011
DOI: 10.1007/s00397-011-0538-1
|View full text |Cite
|
Sign up to set email alerts
|

Melt strengthening of poly (lactic acid) through reactive extrusion with epoxy-functionalized chains

Abstract: International audiencePoly (lactic acid) is an industrially mature, bio-sourced and biodegradable polymer. However, current applications of this eco-friendly material are limited as a result of its brittleness and its poorly melt properties. One of the keys to extend its processing window is to melt strengthen the native material. This paper considers the chain extension as a valuable solution for reaching such an objective. An additive based on epoxy-functionalized PLA was employed during reactive extrusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
134
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(173 citation statements)
references
References 55 publications
12
134
0
4
Order By: Relevance
“…While both PLA and PLA-C samples displayed a narrow monomodal MWD, the PLA-REX spectrum was slightly broadened, the molecular weight increased, and a shoulder appeared in the high molecular weight tail. These changes were expected and are consistent with various published works [68,69]. Since the chain extender is a multifunctional-epoxide agent, these differences were attributed to an increase in the population of high molecular weight linear chains and/or the presence of a mixture of non-uniform branched structures.…”
Section: Molecular Characterizationsupporting
confidence: 91%
See 2 more Smart Citations
“…While both PLA and PLA-C samples displayed a narrow monomodal MWD, the PLA-REX spectrum was slightly broadened, the molecular weight increased, and a shoulder appeared in the high molecular weight tail. These changes were expected and are consistent with various published works [68,69]. Since the chain extender is a multifunctional-epoxide agent, these differences were attributed to an increase in the population of high molecular weight linear chains and/or the presence of a mixture of non-uniform branched structures.…”
Section: Molecular Characterizationsupporting
confidence: 91%
“…According to the literature, PLA-REX samples exhibited the typical behavior of LCB polymers [62,69]. Within the experimental windows, neither |*()| reached a plateau nor G'() reached the theoretical double logarithmic slope of 2.…”
Section: Effect Of Clay And/or Chain Extender Addition On the Rheologmentioning
confidence: 82%
See 1 more Smart Citation
“…Najafi et al [21] prepared PLA-clay nanocomposites using polycarbodiimide, tris(nonyl phenyl) phosphate and Joncryl ADR-4368 as chain extenders. Liu et al [16], Corre et al [22], Mihai et al [23] and Pilla et al [24], employed a multi-functional epoxy-based chain extender (Cesa-Extend from Clariant) to give rise to branched structures of PLA. Recently, Han et al [25] used polysilsesquioxane microspheres as novel chain extenders to improve the thermal stability of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…On one side, reactive extrusion is an attractive way to minimize the degradation effects during processing and to enlarge its processing window. On the other side, Corre et al [11] as well as Pilla et al [12] reported that chain architecture modification by chain branching enhances PLA melt properties. Chain branching degree depends on the functionality of the reactive agent and generally leads to an increase in molecular weight.…”
Section: Introductionmentioning
confidence: 99%